Ontogenetic changes in the venom of Metlapilcoatlus nummifer, the mexican jumping viper - García Osorio, Belem (2020)
The viperid genus Metlapilcoatlus (previously Atropoides) is represented in Mexico by four species: M. olmec, M. mexicanus, M. occidus, and M. nummifer. To date, no studies on their venoms have been reported. Here, we comparatively characterized the venom from M. nummifer neonates (≤8 months of age), young adults (18 months) and adults (≥24 months). We performed biological and enzymatic activities, as well as electrophoretic and RP-HPLC profiling combined with proteomic assignment of major fractions. Venoms from neonates and adults differed in their electrophoretic and chromatographic profiles, indicating that an ontogenetic compositional shift occurs in this species. Protein family assignments showed that neonates produce a venom rich in Snake Venom Metalloproteinases (SVMPs) and Snake Venom Serine Proteases (SVSPs), but lacking Phospholipases A2 (PLA2s). In contrast, adults express abundant venom PLA2s, and lower molecular weight proteins, as evidenced by SDS-PAGE. Functionally, neonate venom did not display PLA2 or procoagulant activities, whereas adult venom did. Hemorrhagic activity was present in both neonate and adult venoms, with similar potencies. Finally, it is of considerable concern that the lethal activity of neither neonate nor adult venoms was neutralized by two therapeutic antivenoms produced in Mexico.